2004
DOI: 10.1093/jn/134.7.1729
|View full text |Cite
|
Sign up to set email alerts
|

Milk-Derived Fatty Acids Are Associated with a More Favorable LDL Particle Size Distribution in Healthy Men

Abstract: A predominance of small dense LDL (sdLDL) particles is a well-established component of the atherogenic lipoprotein phenotype associated with insulin resistance and increased risk for coronary heart disease. However, the influence of diet on LDL particle size distribution is not clear. We investigated (cross-sectionally) the relations between LDL profile and dietary fatty acids (FAs) in 291 healthy men (62-64 y old) with a range of insulin sensitivities. Individuals completed a 7-d dietary record, and fasting p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
73
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(82 citation statements)
references
References 42 publications
8
73
0
1
Order By: Relevance
“…As dairy products, and in particular the full-fat varieties, contribute to the intake of saturated fatty acids, dairy products have generally been suggested to increase CVD risk, although some studies found no association (Tholstrup, 2006) and others found an inverse association between dairy intake and the risk of CVD (Ness et al, 2001) or its risk factors (Samuelson et al, 2001;Pereira et al, 2002;Sjogren et al, 2004). We found no strong evidence that any of the individual full-fat dairy foods was underlying the inverse association between full-fat dairy intake and CVD mortality.…”
Section: Discussionmentioning
confidence: 99%
“…As dairy products, and in particular the full-fat varieties, contribute to the intake of saturated fatty acids, dairy products have generally been suggested to increase CVD risk, although some studies found no association (Tholstrup, 2006) and others found an inverse association between dairy intake and the risk of CVD (Ness et al, 2001) or its risk factors (Samuelson et al, 2001;Pereira et al, 2002;Sjogren et al, 2004). We found no strong evidence that any of the individual full-fat dairy foods was underlying the inverse association between full-fat dairy intake and CVD mortality.…”
Section: Discussionmentioning
confidence: 99%
“…The men were selected to represent a wide range of fasting plasma insulin concentrations. Recruitment details, exclusion criteria, clinical procedures and dietary assessment (7 day dietary records) have been described previously [11]. Subcutaneous adipose tissue biopsies were taken from the left upper buttock for subsequent analysis; smaller biopsies were taken from all individuals for fatty acid composition analysis and larger biopsies were taken from a subset of 87 individuals (equally distributed throughout the tertiles of fasting insulin concentrations).…”
Section: Methodsmentioning
confidence: 99%
“…Laboratory procedures Methods for determination of plasma glucose, insulin, proinsulin, uric acid, triacylglycerol, LDL peak particle size distribution and cholesterol in VLDL, LDL and HDL have been described previously [11]. Circulating levels of oxidised LDL, C-reactive protein (CRP), TNFα and IL-6 were derived as described previously [12].…”
Section: Methodsmentioning
confidence: 99%
“…For this reason, consumption of high fat dairy products would be expected to be associated with CVD risk. However, results of epidemiologic surveys, animal experiments, and human dietary studies have been conflicting [27,28,36,38]. This discrepancy may be ascribed to the differences in the atherogenic effects of various dairy products.…”
Section: Introductionmentioning
confidence: 99%